Phylogenomic analysis of trichomycterid catfishes (Teleostei: Siluriformes) inferred from ultraconserved elements - Ochoa, Luz E. [UNESP]; Datovo, Alessio; DoNascimiento, Carlos; Roxo, Fabio F. [UNESP]; Sabaj, Mark H.; Chang, Jonathan; Melo, Bruno F. [UNESP]; Silva, Gabriel S. C. [UNESP]; Foresti, Fausto [UNESP]; Alfaro, Michael; Oliveira, Claudio [UNESP] (Nature Publishing Group, 2020)
The family Trichomycteridae is one of the most diverse groups of freshwater catfishes in South and Central America with eight subfamilies, 41 genera and more than 300 valid species. Its members are widely distributed throughout South America, reaching Costa Rica in Central America and are recognized by extraordinary anatomical specializations and trophic diversity. In order to assess the phylogenetic relationships of Trichomycteridae, we collected sequence data from ultraconserved elements (UCEs) of the genome from 141 specimens of Trichomycteridae and 12 outgroup species. We used a concatenated matrix to assess the phylogenetic relationships by Bayesian inference (BI) and maximum likelihood (ML) searches and a coalescent analysis of species trees. The results show a highly resolved phylogeny with broad agreement among the three distinct analyses, providing overwhelming support for the monophyletic status of subfamily Trichomycterinae including Ituglanis and Scleronema. Previous relationship hypotheses among subfamilies are strongly corroborated, such as the sister relationship between Copionodontinae and Trichogeninae forming a sister clade to the remaining trichomycterids and the intrafamilial clade TSVSG (Tridentinae-Stegophilinae-VandelliinaeSarcoglanidinae-Glanapteryginae). Monophyly of Glanapteryginae and Sarcoglanidinae was not supported and the enigmatic Potamoglanis is placed outside Tridentinae.